CARACTERÍSTICAS BOTANICAS DE LA RESERVA MILITAR Y ECOLÓGICA ARENILLAS, EL ORO - ECUADOR - Cerón, Carlos (2006)
The study area was the Arenillas Military and Ecological Reserve in the province of El Oro, coordinates 03°25.93’S - 0°06.50’W (Cayancas) and 03°38.59’S - 80°09.94’W (El Cubo). The altitude of the area is between 12 and 120 masl. The botanic research was carried out in June 2002 and was funded by RAMSAR through FEDIMA. We made surveys in several areas throughout the reserve; in each sampling locality we recorded the coordinates and collected botanic samples that were identified and deposited in the Alfredo Paredes Herbarium. We recorded 105 species (including 3 endemic species) of 49 families. The area ¡ncludes 3 life zones and 6 vegetation types. There are 8 seasonal and permanent lacustrine grasslands. The Arenillas Reserve is the Ecuadorian area that better represents the tropical dry forest ecosystems, although it also ineludes mangrove, spiny shrubland and savanna ecosystems.